Atazanavir-induced unconjugated hyperbilirubinemia prevents vascular hyporeactivity during experimental human endotoxemia - Dorresteijn, Mirrin J.; Dekker, Douwe; Zwaag, Jelle; Heemskerk, Suzanne; Roelofs, Hennie M.J.; Smits, Paul; van der Hoeven, Johannes G.; Wagener, Frank A.D.T.G.; Pickkers, Peter (Frontiers in Immunology, 2023)
Objective: Inflammation-induced free radical release is important in the pathogenesis of several diseases, including atherosclerosis and sepsis. Heme oxygenase (HO) breaks down heme into carbon monoxide, iron and biliverdin. Biliverdin IXα is subsequently converted to bilirubin by biliverdin reductase. Unconjugated bilirubin is a powerful antioxidant, and elevated levels have beneficial effects in preclinical models and human cardiovascular disease. However, its impact during acute inflammation in humans is unknown. In the present study, we investigated the effects of atazanavir-induced (unconjugated) hyperbilirubinemia on antioxidant capacity, inflammation, and endothelial dysfunction in human experimental endotoxemia. Approach and Results: Following double-blinded four-day treatment with atazanavir 2dd300 mg (or placebo), twenty healthy male volunteers received 2 ng/kg Escherichia coli lipopolysaccharide intravenously. Blood was drawn to determine the bilirubin levels, antioxidant capacity, and cytokine response. It was demonstrated that following atazanavir treatment, total bilirubin concentrations increased to maximum values of 4.67 (95%CI 3.91-5.59) compared to 0.82 (95%CI 0.64-1.07) mg/dL in the control group (p<0.01). Furthermore, the anti-oxidant capacity, as measured by the ferric-reducing activity of plasma (FRAP), was significantly increased with 36% in hyperbilirubinemia subjects (p<0.0001), and FRAP concentrations correlated strongly to bilirubin concentrations (R2=0.77, p<0.001). Hyperbilirubinemia attenuated the release of interleukin-10 from 377 (95%CI 233-609) to 219 (95%CI 152-318) pg/mL (p=0.01), whereas the release of pro-inflammatory cytokines remained unaltered. In vitro, in the absence of hyperbilirubinemia, atazanavir did not influence lipopolysaccharide-induced cytokine release. Endothelial function was assessed using forearm venous occlusion plethysmography after intra-arterial infusion of acetylcholine and nitroglycerin. Hyperbilirubinemia completely prevented the LPS-associated blunted vascular response to acetylcholine and nitroglycerin. Conclusions: Atazanavir-induced hyperbilirubinemia increases antioxidant capacity, attenuates interleukin-10 release, and prevents vascular hyporesponsiveness during human systemic inflammation elicited by experimental endotoxemia.